“Kia Hiwa Rā!” How Māori-language Journalists Adapt Elements of Whaikōrero for Newswork - Middleton, Atakohu (Te Ara Poutama | Faculty of Maori and Indigenous Development, Auckland University of Technology, 2020)
Aotearoa has a substantial Māori-language news and current affairs sector. A notable aspect of the field is the way in which journalists have imported elements of the ancient and enduring art of whaikōrero, or public oratory, into standard structures of news communication and framing. For example, incantations that are commonly used to open whaikōrero are refashioned to open news shows, and figures of speech based in ancient thought are reinterpreted to illuminate modern concepts. Using textual, intertextual and conversation analysis, this novel paper examines the language of journalists and presenters on four Māori-language news and current affairs programmes to demonstrate how they weave elements of whaikōrero into their on-air work. This paper also discusses the cultural and linguistic issues broadcasters consider.